Design of a Wearable Haptic Device for Hand Palm Cutaneous Feedback - Dragusanu, Mihai; Villani, Alberto; Prattichizzo, Domenico; Malvezzi, Monica (Frontiers in Robotics and AI, 2021)
This paper describes the main design and prototyping steps of a novel haptic device for cutaneous stimulus of hand palm. This part of the hand is fundamental in several grasping and manipulation tasks but is still less exploited in haptics applications than other parts of the hand, as for instance the fingertips. The proposed device has a parallel tendon-based mechanical structure and is actuated by three motors positioned on the hand back. The device is able to apply both normal and tangential forces and to render the contact with surfaces with different slopes. The end-effector can be easily changed to simulate the contact with different surface curvatures. \textcolor{blue}{The design is inspired by a smaller device previously developed for the fingertips, however, in the device presented in this paper, there are significant differences due to the wider size, the different form-factor, and structure of the hand palm. The hand palm represents the support for the fingers and is connected to the arm through the wrist. The device has to be developed taking into account fingers' and wrist's motions, and this requirement constrains the number of actuators and the features of the transmission system. The larger size of the palm and the higher forces challenge the device from the structural point of view. } Since tendons can apply only tensile forces, a spring-based support has been developed to keep the end-effector separated from the palm when the device is not actuated or when the force to be rendered is null. The paper presents the main design guidelines and the main features of the proposed device. A prototype has been realized for the preliminary tests and an application scenario with a VR environment is introduced.